Tears and cheers: A narrative inquiry of a doctoral student’s resilience in study abroad - Wu, Xinxin (Frontiers in Psychology, 2022)
The existing literature has revealed many issues related to Ph.D. students’ wellbeing, such as anxiety and stress, which are likely to cause Ph.D. student attrition or dropout. As one of the key coping strategies against psychological burnout, resilience has received increasing attention among various teacher groups. However, it still lacks a systematic understanding of students, in particular overseas Ph.D. students. This article explores doctoral students’ resilience through a narrative inquiry into the resilience-building process of a Ph.D. student in language and linguistics, Hongxia, in the United Kingdom. Drawing on the research methods and results of resilience from teachers, this study examines Hongxia’s lived experience as a Ph.D. student throughout her 3 years of learning and research and uncovers the dynamic and multifaceted process of resilience building as the interplay between Ph.D. students’ agency, peers, supervisors, academics, families, and friends. The current research supports the value of narrative inquiry, in particular critical story analysis, as a tool for studying the resilience-building processes in Ph.D. students during their candidature. It also hopes to provide insight for administrators, supervisors, and other related stakeholders on their intervention to support and facilitate the research journey of doctoral students.